2012
DOI: 10.1029/2011ja017141
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐spacecraft radio occultation measurement of the electron density near the lunar surface by the SELENE mission

Abstract: [1] During the SELENE (Kaguya) mission the dual-spacecraft radio occultation technique was used to investigate the electron population in the vicinity of the lunar surface. One pair of coherent S-band radio signals from one spacecraft was used to probe the possible electron density enhancement near the Moon, and another signal pair from the other spacecraft measured the solar wind and the terrestrial ionosphere plasma fluctuations, which also exist in the measurement by the former signal pair. The results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
(45 reference statements)
0
13
2
Order By: Relevance
“…Vyshlov [1976] demonstrated that the lunar TEC along RO links can reach ~0.03 TECU, with an estimated peak number density of 10 4 cm -3 at the lunar surface. However, later studies demonstrated RO TEC that does not exceed 0.015 TECU, with a peak density on the order of 10 2 cm -3 [Imamura et al, 2012;Ando et al, 2012;Choudhary et al, 2016]. Integrating vertical density profiles obtained by the latest studies, the vertical TEC is estimated to reach ~0.001 TECU.…”
Section: System and Operational Requirementsmentioning
confidence: 94%
See 1 more Smart Citation
“…Vyshlov [1976] demonstrated that the lunar TEC along RO links can reach ~0.03 TECU, with an estimated peak number density of 10 4 cm -3 at the lunar surface. However, later studies demonstrated RO TEC that does not exceed 0.015 TECU, with a peak density on the order of 10 2 cm -3 [Imamura et al, 2012;Ando et al, 2012;Choudhary et al, 2016]. Integrating vertical density profiles obtained by the latest studies, the vertical TEC is estimated to reach ~0.001 TECU.…”
Section: System and Operational Requirementsmentioning
confidence: 94%
“…The Istituto di Radioastronomia of the Istituto Nazionale di Astrofisica conducted lunar occultation campaigns in 2006-2007 using radio telescopes to observe signals of SMART-1, Cassini, and Venus Express as they occulted the lunar ionosphere, with estimated lunar ionosphere columnar electron content of ~10 13 m -2 said to be "in agreement" with results of the Luna mission [Pluchino et al, 2008]. The SELenological and Engineering Explorer (SELENE; aka Kaguya) mission [Imamura et al, 2008;Imamura et al, 2010] used dual frequency transmissions to observe only a fraction of the electron content observed by Luna, possibly due to either lower solar activity levels comparted to the Luna observation period or the polar observation of SELENE as opposed to lower latitude observations of Luna [Ando et al, 2012]. As the primary error source in satellite-to-Earth RO links arises from variations in the Earth's ionosphere, SELENE also employed dual-satellite observations to alleviate some of this error, where one spacecraft at lunar limb-viewing configuration, with a second spacecraft situated away from the limb monitoring the interplanetary and terrestrial plasma.…”
Section: Introductionmentioning
confidence: 94%
“…Ando et al. (2012) recommended the use of large frequency separations in dual‐frequency techniques for future lunar RO missions, given the large measurement noise present in the SELENE radio occultation experiment. SELENE used frequencies of 2218.0000 MHz and 2287.3125 MHz.…”
Section: Lunar Ro Simulationsmentioning
confidence: 99%
“…Corresponding differential phases shown in panel (d) range from ∼0.008 to ∼0.2 wave cycles at ground level, and from ∼0.0001 to ∼0.008 cycles at 35 km. Lunar RO TEC of Luna 19 and 22 were derived from differential phases on the order of ∼0.04 cycles at S-band frequencies, while SELENE lunar RO TEC was derived from differential phases on the order of ∼0.001 cycles at S-band frequencies(Ando et al, 2012). Larger frequency separations are evidently ideal, even more so since TEC measurements based on larger frequency separations are less sensitive to measurement noise Ando et al (2012).…”
mentioning
confidence: 99%
“…To achieve finite-time convergence of dynamical systems, terminal SMC (TSMC) has been a widely used approach [33,34]. For example, a terminal SMC is applied to design attitude tracking control in [30].…”
Section: Introductionmentioning
confidence: 99%